The daily life of the family living with a crack user - Daiana Foggiato de Siqueira; Claudete Moreschi; Dirce Stein Backes; Luís Felipe Pissaia (Universidade de Santa Cruz do Sul, 2021)
Background and objectives: Drug use is considered a public health problem due to the physical, biological, psychological and social repercussions caused by this phenomenon in the lives of users and society in general. The aim of this study was to describe the daily life of the family living with a crack user. Methods: This is an exploratory-descriptive qualitative study. Data were collected through a focus group with ten family members of crack addicts admitted to a drug detox treatment unit in a hospital in Rio Grande do Sul. Data were analyzed according to content analysis. Results: Based on the analysis of results, two categories emerged, namely "Feelings of family members" and "Living with concerns". Conclusion: Crack addiction weakens family relationships and disrupts the family and social life.